Pengaruh transfer of motor skill learning dari tangan sehat terhadap peningkatan fungsional tangan paresis pasien stroke subakut - ., Elina; Sengkey, Lidwina S. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: This study aimed to demonstrate the effect of transfer of motor skill learning from healthy hand on increasing functional paretic’s hand of stroke patient. This was a descriptive study conducted at the Instalation of Medical Rehabilitation, Prof. Dr. R. D. Kandou Hospital Manado. There were 26 patients of subacute stroke that fulfilled the inclusion criteria. All subjects were trained for 6 weeks and then were evaluated with nine hole peg test dan Sollerman hand function test. The results showed that of the 26 patients, 15 (57.7%) were males. The highest percentages were as follows: mean of age was 57.58 years old (38.5%), onset of stroke was less than 10 weeks (65.4%), and nonhaemorrhagic stroke (88.5%). The Wilcoxon test showed that there were significant differences of nine hole peg test and Sollerman hand function test scores before and after exercise (P <0.001). Conclusion: Transfer of motor skill learning from healthy hand could increase functional paretic hand of stroke patients.Keywords: stroke, transfer of motor skill, bilateral transfer, mirror neuronAbstrak: Penelitian ini bertujuan untuk membuktikan pengaruh transfer of motor skill learning tangan sehat terhadap peningkatan fungsional tangan paresis pasien stroke subakut. Jenis penelitian ini ialah deskriptif. Penelitian dilaksanakan di Instalasi Rehabilitasi Medik RSUP Prof Dr. R. D. Kandou Manado. Sebanyak 26 orang pasien stroke fase subakut yang memenuhi kriteria inklusi. Semua subyek diberi latihan selama 6 minggu kemudian dilakukan penilaian dengan nine hole peg test dan Sollerman hand function test. Hasil penelitian memperlihatkan dari 26 subjek, persentase tertinggi ialah laki-laki sebanyak 15 orang (57,7%), usia rata-rata ialah 57,58 tahun (38,5%), onset terjadinya stroke kurang dari 10 minggu (65,4%), dan stroke non-hemoragik (88,5%). Hasil uji Wilcoxon menyatakan terdapat perbedaan bermakna pada nilai nine hole peg test dan Sollerman hand function test sebelum (awal) dan sesudah (akhir) perlakuan (p <0,001). Simpulan: Transfer of motor skill learning tangan yang sehat dapat meningkatkan fungsional tangan paresis pasien stroke subakut.Kata kunci: stroke, transfer of motor skill, bilateral transfer, mirror neuron